PENGGUNAAN KUTEKS SEBAGAI ALTERNATIF MOUNTING MEDIA PADA PEMBUATAN PREPARAT JARINGAN - Khristian, Erick; Purnama, Jeri Nobia (Faculty of Health Science and Technology, University of Jenderal Achmad Yani, 2020)
Mounting media is one of the important components in making tissue slides. Mounting media serves to cover the tissue on the slide to protect it from damage and also creates a refractive index between the tissue and objective lens approach, so that it can be seen clearly when observed using a microscope. Mounting media commonly used in the laboratory for tissue slide include entelan, Canada balsam and DFX. The aim of this research is to find an alternative mounting media that is cheap, easy to obtain and has a value comparable to the commonly used mounting media. The study used various organs of the liver, kidney, testes and brain stained with Haematoxylin Eosin. The analysis used is descriptive analysis by comparing the quality of the tissue slides using different mounting media, that is entelan and nail polish. The test parameters to see the quality of the results from the use of mounting media are the contrast of the tissue slides, the details of the nucleus and the brightness of the cytoplasm. The results of the study showed comparable values ​​for tissue slide contrast, nucleus detail and the brightness of the cytoplasm for all the organs made. It is advisable to use other stains to ensure that the use of nail polish can be used as a mounting media in the laboratory